Individual ambidexterity: a critical capability towards innovativeness in organisations - Nitsckie, Bradley (Graduate School of Business (GSB), 2022)
Innovation activities vary over time as organisations evolve towards more exploitative innovation to extract maximum performance from existing knowledge and operations. This is a natural evolution, where past innovators become the leaders, capital allocators and managers. Well-run and continuous improvement programmes deeply embed organisational preferences, inadvertently raising barriers to explorative innovation which seeks new knowledges and, with it, a divergence from current thinking. The prospect of new discovery induces paradox as it threatens obsolescence. It seeks high variance, in the face of a low variance focus. Enabling an ambidexterity capability will synergise these tensions and gain the benefits of both types of innovation. Synergising both offers long-term sustained innovation and enhanced performance, and so ambidexterity capability is of significant importance. The researcher's objective is to explore how an individual ambidexterity capability is able to improve an organisation's ability to synergise the paradoxical tensions in the innovation process. This thesis has a focus on how organisations may scale their internal ambidexterity capabilities. Individual ambidexterity proposes a reframing of the role of the individual towards taking a far more central role, and one from which the ambidexterity capability is scaled. It promises a richer, more generative capability which breaks beyond the limits and boundaries of the structural or leadership limitations. This thesis heeds a call for more theorising on how individuals experience paradox tensions and provides revelatory ambidexterity insights into real world of work situations. The work of this thesis has been to enter the real world of work through the interviewing of 12 participants from a selected case study on an explorative innovation, in an environment more familiar with exploitative innovation performance. The researcher also interviewed 3 functional experts to gain insights into current individual capability support and enablement. Through this thesis the researcher's findings contribute that the paradox tensions are complex layers of interrelated tensions, that they have severe implications for the individual in their ability to respond, that this ability to respond should be deliberately supported by competency, trait, behavioural and other capability models, but also that leaders play a critical role in creatings a supportive context for the individual to enact ambidexterity and lastly that there is also a need for the right instrumental support for the varying needs in the innovation process. This thesis supports the notion that with a lack of awareness and intentionality for ambidexterity, individuals are left to face complex paradoxical tensions but their response is left to chance or individual intuition. Their individual ambidexterity is a rich source of sustained innovation capability but requires a strategic approach to enable it. It requires the reframing of the role of the leader in shifting to a supportive and enabling role, emancipating the agency of the individual in creating a supportive organisational context, a context which normalises the empowerment of individuals, exploration, divergence and experimentation. It is critical to ensure that personal career risks do not inhibit the exploration or agency of individuals.